Techno-Economic Analysis of Extractive Butanol Fermentation by Immobilized Cells with Large Extractant Volume - Darmayanti, Rizki Fitria; Muharja, Maktum; Zhao, Tao; Gao, Ming; Tashiro, Yukihiro; Sakai, Kenji; Sonomoto, Kenji (Jurnal Teknik Kimia dan Lingkungan, 2022)
There are several challenges for ABE fermentation to be used in an industrial scale including the low of butanol yield, the high energy requirement for separation and purification, and the competeness of sugar with food demand as substrat. In this study, techno-economical aspects of ABE fermentation by using immobilized cells with large extractant volume were studied. Overall production process was designed using rice straw as raw material which is semi-hydrolyzed to produce cellobiose, glucose, xylose, and arabinose mixture. Concentrated sugar was then fed to extractive fed-batch fermentation using immobilized cells. Finally, extractant was recovered and products were purified by distillation column. By evaluating this process design for the small scale capacity of 238 kg-butanol and acetone/day, the energy requirement was 41.3 MJ/kg-butanol and acetone and the cost was 1.91 $/kg-butanol and acetone. Although the cost was higher than butanol produced by petrochemical process of 1.08 $/kg-butanol, it may reduce if the scale is increased.